2019
DOI: 10.1016/j.amsu.2019.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Gluteal compartment syndrome following alcohol intoxication: Case report and literature review

Abstract: Introduction A compartment syndrome (CS) occurs when increased pressure within an anatomic compartment leads to inadequate perfusion. Although rare, gluteal CS can be encountered when an unconscious person has a prolonged period of immobilization. Presentation of case A 20-year-old male with history of polysubstance abuse leading to passing out, presented with right buttock and lower extremity pain, increased creatinine phosphokinase (CPK), and acute renal failure. Phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 13 publications
(15 reference statements)
0
20
0
Order By: Relevance
“…Optimal prognosis is associated with performing a fasciotomy within 6 hours of presentation. 4 A fasciotomy decreases the intra-compartmental pressure, allowing for proper perfusion of the patient’s tissues. It is important to release the fascia along the entirety of the compartment to prevent incomplete release and continued tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Optimal prognosis is associated with performing a fasciotomy within 6 hours of presentation. 4 A fasciotomy decreases the intra-compartmental pressure, allowing for proper perfusion of the patient’s tissues. It is important to release the fascia along the entirety of the compartment to prevent incomplete release and continued tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Depressants, including alcohol and heroin, have been described in the literature in multiple case reports as direct causes of obtundation and immobility leading to compartment syndrome. [3][4][5][6][7] Other substances such as synthetic cannabinoids or K2 have been less frequently described as being associated with compartment syndrome. In one study from Turkey, Ergul et al describes six cases in which synthetic cannabinoids were directly linked to cases of renal failure, rhabdomyolysis and compartment syndrome.…”
Section: Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…1 Any of the three gluteal compartments, the anterior tensor fascia lata compartment, the gluteus medius and minimus compartment, or the posterior gluteus maximus compartment, can be affected. 2 Approximately 50% of cases are due to prolonged immobilization secondary to surgery, or alcohol or substance use. 3 Benns et al showed that compartment syndrome in patients with opioid use disorder (OUD) was more likely to be gluteal (31.8%) when compared to other etiologies and led to prolonged hospital admissions.…”
Section: Introductionmentioning
confidence: 99%
“…Compartment syndrome is an acute surgical emergency, with one common etiology being prolonged immobilization secondary to overconsumption of opioids [1]. These patients provide a unique subset of management challenges.…”
Section: Introductionmentioning
confidence: 99%